The irony of RH law critics' opposition to comprehensive sex education - Michael R.M. Abrigo; Vicente B. Paqueo (Philippine Institute for Development Studies (PIDS), 2016)
Sex-related risks, early sexual experience, and unwanted pregnancies are major concerns of Filipinos. These issues have long been battle grounds for the often rancorous debates about the provisions of the Reproductive Health (RH) Law. In December 2012, Congress approved a comprehensive RH Law that guarantees universal access to services, including age-appropriate health and sexuality education in schools. Critics then raised a public health concern, saying that exposing children to reproductive health care, especially mandatory sexuality education, leads to earlier sexual initiation and higher rates of sexual activity among them. Using the 2008 National Demographic and Health Surveys, this paper analyzes how sex education relates with the sexual behavior of women 15-24 years old. Our analysis of sexual behaviors by young adult females in recent national surveys does not corroborate this claim. Ultimately, it is ironic that their future is being jeopardized by well-meaning opposition to the RH Law, which calls for keeping women better informed about sex-related risks, unwanted pregnancies, their consequences, and ways of avoiding them.
Keywords: 330; Philippines; health; reproductive health; sexuality education; Reproductive Health Law; sex-related risks